A Teoria das inteligências múltiplas no ensino e aprendizagem de língua inglesa na escola pública - Ferrão, Marco Antonio Fonseca [UNESP] (2006)
This research study aimed at investigating how the Multiple Intelligences theory (MI), proposed by Howard Gardner, can help de design and implementation of teaching practices in English language teaching in public schools. An important aspect of this proposal is to consider the students' different skills and capacities, and their many manifestations as valuable products in the students' context. An action-research project was conducted with a first-year class of a state high school in Brazil, for two semesters. Didactic activities were adapted, on the basis of the MI theory, and used in that context. Data were collected by means of an inventory of intelligences, questionnaires, diaries and observations made by the teacher-researcher, and lessons were recorded. The theoretical bases of the MI theory and of the Communicative Approach, followed during the lessons, are presented here, as well as the research methodology, examples of the class activities, the results of the study and a reflection about the data. In the context investigated, this study focuses on possible solutions for the problems faced in the teacher's work and, by promoting reflection and discussion about pedagogical practices, expects to create conditions for better teaching conditions and the development of new and better strategies for the teaching of foreign languages.